KUALITAS BEBERAPA TELUR BERMEREK KHUSUS DIBANDINGKAN DENGAN TELUR AYAM RAS DAN BURAS - Rossi R.S. Apriyantono; Nelis Imanningsih; Uken S.S. Soetrisno (Persagi, 1999)
Quality of Branded Eggs as Compared to Layer and Domestic Chicken Eggs.Many branded eggs found in the market claimed as low in cholesterol (Low Cholesterol Egg, Golden Egg), or claimed as high in omega-3 fatty acid content (Omega-3 Egg), besides common domestic and layer chicken eggs. This brand trend attracted the consumer to buy. Nonetheless, there is a need to evaluate further on the quality they claimed besides the physical quality. The evaluation was done regarded of those 5 types of eggs on their outer measurements (shape abnormalities, size indexes, shell thickness); and inner measurements (Haugh Units, yolk color score). The results indicated that all egg types had normal appearance with size indexes of 1.24-1.38. The Haugh Units was arround 28.7-67.3 and yolk color score was arround 5.0-13.3. Based on those results, the zerro week marketed eggs (Group I) clasified as A quality and the one week marketed eggs (Group II) were B quality. The data on chemical analyses indicated that the omega-3 fatty acid content was significantly the highest (p<0.05) in Omega-3 egg, while the cholesterol content was 'similar in all types of eggs. The easiest way to judge the quality are from the shape and size of the eggs. Those have to be in normal shape and uniform size. While the claimed on low cholesterol content is not proven.Keywords: cholesterol content, omega-3 content, physical quality, chicken eggs.